Islamic Leadership: Prophet Muhammad as a Role Model for being Charismatic, Transformational and Servant Leader - Kamaluddin Kamaluddin; Putri Rizka Citaningati (AIBPM Publisher, 2023)
A well-functioning organization or company requires a capable leader who can effectively motivate and influence the people around them. Numerous leadership models serve as the foundation for appointing leaders in different organizations. For a devout Muslim, the Prophet Muhammad SAW serves as an exemplary leader. This qualitative study, utilizing a literature review method, aims to uncover the leadership traits of the Prophet Muhammad SAW within three leadership models: Charismatic Leadership, Transformational Leadership, and Servant Leadership. Consequently, this research will offer valuable perspectives to the community and aspiring leaders, guiding them in adopting the admirable qualities and behaviors demonstrated by the Prophet Muhammad SAW.